High strength adhesives from sustainable components

The problem of difficulty in recycling and toxicity of existing adhesive materials is solved by developing adhesive compositions containing epoxidized oils, nucleophiles and phenolic compounds, and the goal of high-strength bonding and sustainable development has been achieved.

CN119403898APending Publication Date: 2025-02-07PURDUE RES FOUND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038475.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-05
Filing Date
2023-05-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing adhesive materials are derived from petroleum and are difficult to recycle and are toxic, resulting in environmental pollution and health risks. Bio-based alternative adhesives are costly and poor in performance, making them difficult to supply on a large scale.

Method used

A binder composition is developed, including epoxidized oil, nucleophilic reagents and phenolic compounds, to form a high-strength binder by heating and mixing reaction, employing sustainable biosource components to reduce environmental impacts.

Benefits of technology

High strength bonding is achieved, environmental pollution is reduced, sustainable material solutions are provided, and are cost-effective and easy to supply at a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403898A_ABST
    Figure CN119403898A_ABST
Patent Text Reader

Abstract

A high strength adhesive composition comprising components such as (i) an epoxidized oil, (ii) a nucleophilic agent, and (iii) a phenolic compound from low cost biomaterials of sustainable sources that can be obtained on a large scale; uses thereof; and a manufacturing method.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 338,465, filed on May 5, 2022, which is incorporated herein by reference in its entirety. Government Support Statement

[0002] This invention was made with Government support under Grant No. N00014-19-1-2342 awarded by the Office of Naval Research. The Government may have certain rights in this invention. Technical Field

[0003] The present disclosure relates to high-strength adhesives made using sustainable components. In particular, the present disclosure relates to high-strength adhesives comprising bio-based materials that can enhance recycling and enable a sustainable material ecosystem. Background Art

[0004] This section introduces various aspects that may be helpful in better understanding the present disclosure. Therefore, these statements should be read in this light and not as admissions of what is or is not prior art.

[0005] From electronic devices to furniture, most consumer products are held together with adhesives. High performance, versatility and low cost are the hallmarks of modern adhesives. However, these properties also bring with them some environmental concerns. These materials are derived from petroleum, produce permanent bonds, are difficult to chemically degrade and are toxic. Due to this unnatural origin of adhesives, most components cannot be separated for recycling. Non-degradable bonds make the substrates inseparable, impossible to recycle and force the products into landfills. These discarded adhesive resins further contribute to the problem of marine microplastics. Toxicity is also a problem, for example, adhesives in plywood release carcinogenic formaldehyde. Society is saturated with single-use products and packaging. Biomimetic chemistry inspired by shellfish adhesives provides the required crosslinks. Bio-derived adhesives can provide the needed pathway to a sustainable materials ecosystem.

[0006] Cost and performance compared to modern materials are long-standing issues for bio-based alternative adhesives. In the case of bio-adhesives, availability further hinders their sustainability. The components of bio-based materials are not easy to manufacture on a large scale. Therefore, they have not been adopted by the industry.

[0007] Therefore, there is an unmet need for a high-strength adhesive that is easily recyclable, safe for the ecosystem, low in cost, made using bio-based materials, and easily available on a large scale. An object of the present disclosure is to provide such an adhesive. This and other objects, advantages, and inventive features will be apparent from the detailed description provided herein. Summary of the invention

[0008] An adhesive composition is provided, which comprises (i) epoxidized oil (EO), (ii) a nucleophile and (iii) a phenolic compound.

[0009] The epoxidized oil can be any suitable epoxidized oil obtained from a sustainable source. In some embodiments, the sustainable source can be a plant or vegetable. In some embodiments, the epoxidized oil is epoxidized soybean oil.

[0010] The nucleophile can be a compound comprising a moiety selected from the group consisting of an acid, an alcohol, an amine, and a thiol. In some embodiments, the nucleophile can be selected from fumaric acid, glycerol, malic acid, succinic acid, or a combination thereof. In some embodiments, the nucleophile is malic acid.

[0011] The phenolic compound may be selected from catechol, gallic acid, gallol, lignin, tannic acid or a combination thereof. In some embodiments, the phenolic compound is tannic acid.

[0012] In some embodiments, the adhesive composition may optionally further comprise a solvent. Examples of solvents include, but are not limited to, alcohol, water, chloroform, dichloromethane, dimethyl sulfoxide, and dimethylformamide. In some embodiments, the solvent may be an alcohol, such as ethanol or methanol.

[0013] In some embodiments, EO, the nucleophile, and the phenolic compound may be present in a mass ratio of about 1:0.1:0.1 to about 1:10:10.

[0014] In some embodiments, the adhesive composition consists essentially of (i) epoxidized soybean oil (ESO), (ii) malic acid, (iii) tannic acid, and (iv) ethanol. ESO, malic acid, and tannic acid are present in a mass ratio of about 1:0.1:0.1 to about 1:10:10.

[0015] A method of making an adhesive composition is provided, the method comprising: i) heating epoxidized oil (EO); ii) mixing a phenolic compound with the epoxidized oil of step (i) to obtain a solution, wherein the phenolic compound is optionally It exists in the form of a solution in a solvent; iii) adding a nucleophile to the solution of step (ii) and heating the solution; and iv) cooling the solution to room temperature, Thus, an adhesive composition was obtained.

[0016] The EO may be heated at a temperature of about 70° C. to about 90° C. to obtain a desired viscosity. The solution of step (iii) may be heated at a temperature of about 70° C. to about 90° C. The solution may be heated overnight and cooled to room temperature to obtain an adhesive composition.

[0017] Adhesive compositions can be used for bonding substrates. The substrate can be exposed to dry, wet, moist or underwater conditions. The substrate can be selected from metal substrates (such as steel or aluminum), wood, plastics (such as polyvinyl chloride (PVC) or polytetrafluoroethylene (Teflon)), ceramics or a combination thereof. In some embodiments, the metal substrate can be steel or aluminum.

[0018] Provided is a method for using an adhesive composition, the method comprising applying the adhesive composition to at least a first substrate, the first substrate being bonded to at least a second substrate, and bonding at least the first substrate and at least the second substrate to each other. The method further comprises applying the adhesive composition to at least the second substrate before bonding at least the first substrate and at least the second substrate. At least one of the substrates is exposed to dry, moist, wet, or underwater conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present disclosure will be more readily understood from the following detailed description of embodiments in conjunction with the accompanying drawings, in which:

[0020] Figure 1 Adhesion is shown as a function of different ratios between the epoxidized soybean oil, glycerol and tannic acid (soy-gly-tan) components. The substrate is untreated aluminum and the cure was at 180°C for 24 hours.

[0021] Figure 2 Adhesion is shown as a function of different ratios between the epoxidized soybean oil, malic acid and tannic acid (soy-mal-tan) components. The substrate is untreated aluminum and the cure was at 180°C for 24 hours.

[0022] Figure 3 Shown is the adhesion of soy-mal-tan to a polished steel substrate over time when cured at 180°C.

[0023] Figure 4A Shown are the adhesion values ​​of soy-mal-tan compared to commercial adhesives to a polished steel substrate.

[0024] Figure 4B Shown are the adhesion values ​​of soy-mal-tan compared to commercial adhesives to a grit-blasted aluminum substrate.

[0025] Figure 5 Shows the adhesion values ​​of soy-mal-tan to a polyvinyl chloride (PVC) substrate compared to commercial adhesives. The bar graph for Super Glue shows the force at which the PVC substrate breaks.

[0026] Figure 6The bonding performance of sustainably sourced adhesives is shown. A) shows the lap shear bonding of soy-mal-tan to sandblasted steel, B) shows the lap shear bonding of soy-mal-tan to polished aluminum, C) shows the lap shear bonding of soy-mal-tan to teflon, and D) shows the lap shear bonding of soy-mal-tan to a pine substrate. In each case, a comparison was made to a commercial adhesive cured according to the manufacturer's instructions. The soy-mal-tan bond to the metal substrate was cured for 6 hours at 180°C, while the teflon substrate was cured for 24 hours at 180°C. Curing of the wood bond was continued for three days at 120°C. Figure E) shows how the use of soy-mal-tan causes the wood substrate to fail before the adhesive bond breaks.

[0027] Figure 7 Scanning electron microscope (SEM) images of the adhesive after it was pulled to failure are shown. The commercial epoxy shows a clean fracture and distinct regions of the adhesive and substrate. The soy-mal-tan material shows a more complex failure with stress lines indicating ductile behavior. Both substrates are polished steel. The soy-mal-tan adhesive was cured at 180°C for 6 hours.

[0028] Figure 8 Shown is the appearance of the soy-mal-tan system at different stages. A) Epoxidized soybean oil, malic acid and tannic acid after initial mixing at room temperature. B) Soy-mal-tan after 24 hours of reaction at 70°C. The adhesive precursor was kept at 70°C and was viscous but flowable. C) After 24 hours of reaction at 70°C, cooling to room temperature resulted in an increase in viscosity. D) Hardened after curing at 180°C for 24 hours, with the substrate scraped off.

[0029] Fig. 9 Characterization of soy-mal-tan is shown. A) Representation of the components, combinations and final formulations in DMSO-d6 1 HNMR spectra. B) shows malic acid, selected reaction products and soy-mal-tan in DMSO-d6 13 C NMR spectrum. Diethyl malate is provided as an ester reference. C) shows the infrared spectrum in the carbonyl (C=O) region. D) shows the infrared spectrum in the acid (CO-OH) region.

[0030] Fig.10A) shows the water resistance of soy-mal-tan to artificial seawater. Bonded pairs of polished aluminum substrates with an overlap area of ​​1.2x1.2 cm were cured in air at 70°C for 24 hours or at 180°C for 6 hours and then immersed in water for different time periods. The x-axis is a logarithmic graph with units of minutes and units of hours are labeled for clarity. B) shows a pickup truck rocker panel with steel parts bonded together using rivets (top) and soy-mal-tan (bottom). The top of each assembly is secured by rope (beige). A 15-pound weight is hung from the bottom.

[0031] Fig.11 Shown is a test of the resistance of a soy-mal-tan bond to boiling water. The substrate used was polished aluminum. DETAILED DESCRIPTION

[0032] In order to promote the understanding of the principles of the present disclosure, reference will now be made to the embodiments shown in the accompanying drawings and these embodiments will be described using specific language. The description of these embodiments is not intended to limit the scope. On the contrary, the present disclosure is intended to cover alternatives, modifications and equivalents that may be included in the spirit and scope of the present application as defined by the appended claims.

[0033] The terms "adhesive" and "adhesive composition" are used interchangeably.

[0034] The term "phenolic compound" refers to a compound having at least one aromatic ring in the chemical structure, to which one or more hydroxyl groups are attached. "Phenolic compound" may also include polyphenols, which may have more than one aromatic ring, to which one or more hydroxyl groups are attached.

[0035] As is well known, epoxy adhesives are formed by reacting multifunctional epoxide-containing compounds (such as bisphenol A diglycidyl ether) with polyamines (including triethylenetetramine). Nucleophilic amines open the three-membered epoxy ring and generate CN bonds to form an extensively cross-linked matrix. Soybean oil is one of the most extensive renewable organic sources and is a substitute for epoxy resins. A simple reaction of soybean oil with acid and hydrogen peroxide produces epoxidized soybean oil. This is a low-cost bio-based material that can be easily supplied on a large scale. However, epoxidized soybean oil can only produce viscous oil after reacting with polyamines, which is not conducive to adhesion, so it cannot directly replace bisphenol A diglycidyl ether.

[0036] Marine mussels glue themselves to rocks using proteins containing 3,4-dihydroxyphenylalanine (DOPA). These DOPA groups enable the protein to adhere to surfaces via hydrogen bonding and metal chelation, as well as several other interactions. In addition, these side-chain dihydroxyphenyl (i.e., catechol) groups, when oxidized, produce crosslinks that provide cohesive interactions. Thus, epoxidized soybean oil can be transformed into a strong adhesive when chemicals like catechol are added to the adhesive formulation.

[0037] In view of the above, the present disclosure provides an adhesive composition comprising (i) epoxidized oil (EO), (ii) a nucleophile and (iii) a phenolic compound. In an embodiment thereof, the adhesive composition consists essentially of or consists of (i)-(iii).

[0038] Such adhesive compositions may be high strength adhesives comprising components from sustainable bio-sources. The bio-sources may be agricultural raw materials that are low cost, readily available on a large scale, and easily recyclable.

[0039] The epoxidized oil may be any suitable epoxidized oil obtained from a sustainable source. The sustainable source may be a plant or vegetable. In some embodiments, the epoxidized oil is epoxidized soybean oil (ESO).

[0040] ESO can be made from soybean oil. Soybean oil can be obtained from soybean plants, while nucleophiles and phenolic compounds can be obtained from other sustainable natural sources. Therefore, the adhesive can be non-toxic and debondable.

[0041] Nucleophiles are any suitable multifunctional bio-based nucleophiles that can open the epoxy ring. Examples of nucleophiles include, but are not limited to, compounds comprising a portion selected from the group consisting of an acid, an alcohol, an amine, and a thiol. In some embodiments, the nucleophile is selected from fumaric acid, glycerol, malic acid, succinic acid, or a combination thereof. In an exemplary embodiment, the nucleophile is malic acid.

[0042] The phenolic compound may be selected from catechol, gallic acid, gallol, lignin, tannic acid or a combination thereof. Phenolic compounds, such as tannic acid, contain abundant reactive terminal phenolic hydroxyl groups, which have a hyperbranched aromatic / alicyclic polyester core and can form a highly cross-linked network with ESOs having highly reactive epoxy groups. In an exemplary embodiment, the phenolic compound is tannic acid.

[0043] The adhesive composition may further include a solvent. In some embodiments, when the phenolic compound used is tannic acid, the adhesive composition may include a solvent. Therefore, the use of a solvent in the adhesive composition may be optional. In its embodiment, the adhesive composition may further be substantially composed of a solvent (or may further be composed of a solvent).

[0044] Any suitable solvent that can dissolve tannic acid can be used. Examples of solvents include, but are not limited to, alcohols (such as ethanol or methanol), water, chloroform, dichloromethane, dimethyl sulfoxide, and dimethylformamide. In some embodiments, the solvent is ethanol.

[0045] In some embodiments, EO, nucleophile and phenolic compound can be present in a mass ratio of about 1:0.1:0.1 to about 1:10:10 (e.g., about 1:0.1:0.1 to 1:10:10, 1:0.1:0.1 to about 1:10:10, or 1:0.1:0.1 to 1:10:10). In some embodiments, EO, nucleophile and phenolic compound can be present in a mass ratio of about 1:0.3:0.3 to about 1:0.6:0.6 (e.g., about 1:0.3:0.3 to 1:0.6:0.6, 1:0.3:0.3 to about 1:0.6:0.6, or 1:0.3:0.3 to 1:0.6:0.6). Ideally, EO, nucleophile and phenolic compound can be present in a mass ratio of about 1:0.4:0.5 (e.g., 1:0.4:0.5).

[0046] In some embodiments, a maximum strength adhesive composition is provided, the composition comprising (i) ESO, (ii) malic acid, and (iii) tannic acid ("soy-mal-tan"). ESO, malic acid, and tannic acid may be present in a mass ratio of about 1:0.1:0.1 to about 1:10:10 (e.g., about 1:0.1:0.1 to 1:10:10, 1:0.1:0.1 to about 1:10:10, or 1:0.1:0.1 to 1:10:10). In some embodiments, ESO, malic acid, and tannic acid may be present in a mass ratio of about 1:0.3:0.3 to about 1:0.6:0.6 (e.g., about 1:0.3:0.3 to 1:0.6:0.6, 1:0.3:0.3 to about 1:0.6:0.6, or 1:0.3:0.3 to 1:0.6:0.6). Ideally, ESO, malic acid and tannic acid can be present in a mass ratio of about 1:0.4:0.5 (e.g., 1:0.4:0.5). The adhesive composition can further include an organic solvent, such as an alcohol. In some embodiments, the alcohol is ethanol or methanol. The amount of the organic solvent (e.g., ethanol) is about 0.4 g (e.g., 0.4 g) per gram of soy-mal-tan. In its embodiment, the adhesive composition is substantially composed of soy-mal-tan and ethanol or is composed of soy-mal-tan and ethanol.

[0047] Epoxidized oils, nucleophiles, and phenolic compounds form covalent bonds and a highly cross-linked matrix, which contributes to high-strength bonding.

[0048] The adhesive composition can be made by reacting EO, a nucleophile and a phenolic compound. ESO, a nucleophile (such as malic acid) and a phenolic compound (such as tannic acid) can be reacted together to obtain an adhesive composition (such as soy-mal-tan). ESO, malic acid and tannic acid can be represented by the structure shown below. In some embodiments, reacting these three components together can obtain a high-strength and sustainable source adhesive.

[0049] A method of making an adhesive composition is provided, the method comprising: i) heating epoxidized oil (EO); ii) mixing a phenolic compound with the epoxidized oil of step (i) to obtain a solution, wherein the phenolic compound is optionally present in the form of a solution in a solvent; iii) adding a nucleophile to the solution of step (ii) and heating the solution; and iv) cooling the solution to room temperature, Thus, an adhesive composition was obtained.

[0050] The reaction can be carried out at about 20°C to about 90°C, e.g., about 20°C to 90°C, 20°C to about 90°C, or 20°C to 90°C. Ideally, the reaction is carried out at about 20°C to about 70°C, e.g., about 20°C to 70°C, 20°C to about 70°C, or 20°C to 70°C. The reaction can be carried out for about 6 hours to about 24 hours, e.g., about 6 hours to 24 hours, 6 hours to about 24 hours, or 6 hours to 24 hours. This simple mixing and heating process can be easily carried out on a large scale.

[0051] Any suitable solvent that dissolves tannic acid can be used. Examples of solvents include, but are not limited to, alcohols (such as ethanol or methanol), water, chloroform, dichloromethane, dimethyl sulfoxide, and dimethylformamide. In some embodiments, the solvent is ethanol.

[0052] In some embodiments, EO can be heated at a temperature of about 70°C to about 90°C to reduce viscosity. React at 70°C for 24 hours to obtain an amber flowing gel adhesive composition for application between substrates. The heated material can be placed between substrates and cured to form a final adhesive. The adhesive can be cured for about 1 hour to about 24 hours at about 20°C to about 180°C (e.g., about 20°C to 180°C, 20°C to about 180°C, or 20°C to 180°C), for example, about 1 hour to 24 hours, 1 hour to about 24 hours, or 1 hour to 24 hours. When cured at about 180°C for about 24 hours, the adhesive can achieve very high bonding strength. After curing (180°C, 24 hours), the adhesive can become a hard black solid.

[0053] Further provided is a method of using the adhesive composition, the method comprising applying the adhesive composition to at least a first substrate to be bonded to at least a second substrate, and bonding at least the first substrate and at least the second substrate to each other. The method further comprises applying the adhesive composition to at least the second substrate before bonding at least the first substrate and at least the second substrate.

[0054] The adhesive composition may be used when the first substrate and / or the second substrate is exposed to dry, damp, wet, or underwater conditions.

[0055] The substrate for bonding can be selected from metal (such as steel or aluminum), wood, plastic (such as polyvinyl chloride (PVC) or polytetrafluoroethylene (Teflon)), ceramic or any combination thereof. The metal substrate can be polished or sandblasted. In some embodiments, the metal substrate can be steel or aluminum.

[0056] Figure 3 The curing profile is shown for adhesives placed between two pieces of steel and cured at 180°C for 1, 3, 6, 18 or 24 hours. The bond strength at 180°C was significantly stronger than at 70°C or room temperature (Table 1). A 24 hour cure time provided the strongest bond, however a 6 hour cure provided similar bond strengths with a lower carbon footprint from the heat. Table 1. Shows the adhesion of soy-mal-tan on different substrates and curing conditions.

[0057] The bonding properties of the adhesive were examined using aluminum and steel substrates. Figure 4A and Figure 4B The bonds were shown to be generally consistent with structural strength (e.g., >1 MPa), ranging from 10 ± 1 MPa for sandblasted aluminum to 16 ± 1 MPa for polished steel. The structural strength of polished aluminum and sandblasted steel was about 13 MPa. The adhesive controls containing only two components were significantly weaker, or did not bond at all. The adhesion of epoxidized soybean oil to malic acid (no tannic acid) was 1.9 ± 0.4 MPa. Malic acid and tannic acid (no epoxidized soybean oil) formed a hard solid without any bonding ability. Epoxidized soybean oil with tannic acid (no malic acid) never cured to a solid.

[0058] Products require a certain level of water resistance to ensure they remain intact when faced with harsh conditions. However, the water resistance of current industrial adhesives hinders debonding, component recycling, and degradation in landfills. To understand the debonding of adhesives, water resistance studies were conducted. The water used for underwater environmental testing is seawater. The substrate can be immersed in water during or after the application of the adhesive. Water resistance studies have shown that when the substrate is submerged for one week, the substrate will gradually debond over time. Fig.10It was shown that soy-mal-tan maintained about 75-100% of the initial dry bond strength when the substrate was submerged in water for 24 hours. After one week in water, about 26-78% of the bond was retained.

[0059] The adhesive composition can be used as a high strength adhesive for automotive, construction and electronic applications. The adhesive composition can be used to bond parts of a vehicle, wherein the vehicle can be a car.

[0060] Lightweighting of cars and trucks is an example where adhesives can provide additional environmental benefits. Switching from heavy rivets and welds to adhesive bonding can reduce vehicle weight and improve fuel efficiency. Fig.10 Shows how a pickup truck rocker panel is riveted to a steel bar section representing the vehicle frame and demonstrates the performance of the soy-mal-tan adhesive in joining the substrates. The adhesive was cured for five minutes using a heat gun. By replacing 36.9 grams of steel rivets with 0.9 grams of glue, the mass of adhesive in these assemblies was reduced by approximately 97%.

[0061] Sustainability goals for the material include both having bio-based starting components as well as low levels of energy input. Soy-mal-tan cures at 180°C for 6 hours. In comparison, epoxy resins are cured using a wide range of conditions. It has been observed that epoxy resins do not achieve full cure if left at room temperature alone. Automotive, construction and electronics applications account for a large proportion of epoxy resin consumption, and common conditions can use 120-180°C for 30 minutes. Example Material

[0062] Epoxidized soybean oil (ESO) 450 lbs was purchased from Chemical Company. DL-malic acid, fumaric acid, succinic acid, glycerol, tannic acid, gallic acid, and lignin were purchased from Sigma-Aldrich and used without modification. Pyrocatechol was purchased from Acros and used without modification. Example 1

[0063] Synthesis of Epoxidized Soybean Oil-Malic Acid-Tannic Acid (Soy-Mal-Tan) 1.0 g of ESO was added to a 20 mL glass vial with a magnetic stir bar and heated in an oil bath at 70 °C. After sufficient heating to reduce the viscosity, 1 mL of 0.5 g / mL tannic acid / EtOH solution was added to the ESO and mixed for about 5 minutes. 0.4 g of malic acid was then slowly added to the solution until it was completely dissolved. The reaction was heated overnight and removed from the oil bath and cooled to room temperature. At this point, the adhesive was amber in color, free flowing while still warm, and gradually hardened until room temperature. Example 2

[0064] Synthesis of Epoxidized Soybean Oil-Glycerol-Tannic Acid (Soy-Gly-Tan) Soy-Gal-Tan was prepared using the procedure of Example 1 using epoxidized soybean oil, glycerol and tannic acid. Preparation of Adherend

[0065] Metal The steel used is low carbon steel, conforming to ASTM A109 standard. The aluminum is 6061 alloy, conforming to ASTM B209 standard.

[0066] Polishing base Polished ASTM aluminum and stainless steel bonds (12mm x 3.175mm x 89mm) were polished using various metal polishing rods and wheels. The stainless steel bond was polished with a black diamond rod and then a regular green rod. Since aluminum is relatively soft, only brown tripoli bars were used to prepare polished aluminum. After polishing, excess grease was wiped off and all substrates were cleaned using a progressive solvent system consisting of n-hexane, acetone, MeOH, and deionized water. The substrates were dried overnight before use.

[0067] Sandblasting base ASTM aluminum and stainless steel bonds were prepared by placing them in a sandblaster using an abrasive consisting of fine glass bead media. The glass beads were used to create a rough surface on the substrates to allow for a direct comparison of how soy-mal-tan would perform at either a smooth or rough interface.

[0068] Low energy plastic Polyvinyl chloride (PVC) and polytetrafluoroethylene (Teflon) substrates were cut into (12mm x 12mm x 89mm) blocks. Neither material required any special preparation prior to use in adhesive testing.

[0069] wood Cut the pinewood block into the size of 12mm x 12mm x 89mm. The surface of the pinewood base is simply processed with 60-grit sandpaper.

[0070] Application of adhesive to substrate 50 mg of soy-mal-tan was added to each pair of lap shear substrates. The material was applied while it was warm, as the viscosity provided ease of use. A second bond was placed on the first bond, forming an overlap area of ​​approximately 12 mm x approximately 12 mm. The lap shear joints were clamped together to allow the soy-mal-tan to spread between the substrates. After cooling to room temperature, the material hardened between the substrates. These bonds were placed in an oven at 180°C for 6 hours for high energy substrates and 24 hours for Teflon. Due to the melting point of PVC plastic, this plastic sample was placed in a lower temperature oven (110°C) for 24 hours. After curing at 180°C, the soy-mal-tan was dark brown / black and harder than after the initial reaction.

[0071] Adhesion test Bond strength was initially determined using an Instron 5544 equipped with a 2 kN load cell. For samples that exceeded the capacity of the load cell, measurements were made using an MTS Insight materials testing instrument equipped with a 10 kN load cell or an Instron 34TM-30 instrument equipped with a 30 kN load cell. The Instron and MTS samples were placed in the instrument and each bond was held in place using two steel crossbars (e.g., drill blanks). The crossbars were pulled apart at a pull rate of 2 mm / min to stress the joint. The maximum force applied to the joint before failure was recorded in Newtons (N). The maximum force (N) was divided by the joint overlap area (m 2 ), the bond strength is calculated in megapascals (MPa). The reported adhesion data is the average of a minimum of 10 samples, and the error bars represent 90% confidence intervals. One exception is n=5 for the EMT water resistance test. In cases where the joints fell apart as soon as they were picked up, these samples were assigned a value of zero when calculating the average.

[0072] Artificial seawater Aquacraft marine environment salt mix is ​​used to create artificial seawater. The salt is dissolved into reverse osmosis purified water, with a final salinity of 28-30ppt as measured by a refractometer. The water is aerated for at least seven days before use.

[0073] Characterization IR spectrum

[0074] Infrared spectra were obtained using a Thermo Nicolet Nexus FT-IR with Diamond and ZnSe ATR. The MCT detector was used from 800–4500 cm -1 Data are collected for solid samples and analyzed to determine the disappearance of functional groups.

[0075] Infrared (IR) spectroscopy showed that the reaction of malic acid with epoxidized soybean oil in the presence and absence of tannic acid showed a similar bonding scheme, namely, a potential acid-ester transition (about 1680 to about 1720 cm -1 )( Fig. 9 After combining with epoxidized soybean oil, the carboxylic acid CO-OH bands of malic acid (1408, 1278 cm -1 ) is not obvious either. NMR spectroscopy

[0076] Samples for NMR studies were prepared using DMSO-d6 solvent and run using an Oxford 300 MHz magnet. 1 H-NMR and 13 C-NMR and subsequent analysis using Mestrenova software. Individual spectra were peak separated to observe the appearance or disappearance of specific groups.

[0077] According to proton nuclear magnetic resonance ( 1 H NMR) spectra, the initial epoxy groups in the epoxidized soybean oil disappeared after reaction with malic acid, or to a lesser extent after reaction with tannic acid ( Fig. 9 ). Acid titration further confirmed the consumption of epoxy groups during the reaction with malic acid and tannic acid. 1 The presence of alcohol (3.38 ppm) can also be seen in the H NMR spectrum, which is a characteristic result of the opening of the epoxide ring after reaction with a nucleophile. 1 The H NMR alcohol resonance never changes, indicating that the acid groups are produced by the reaction of malic acid with the epoxide. 13 C NMR spectra indicated that the epoxidized soybean oil + malic acid + tannic acid (about 172.2 ppm) or epoxidized soybean oil + malic acid (about 172.5 ppm) ( Fig. 9 B) A small shift in the formation of aliphatic esters supports acid + epoxy coupling. The presence of multiple broad peaks indicates the formation of a cross-linked and heterogeneous system. Differential Scanning Calorimetry (DSC)

[0078] Differential scanning calorimetry was performed using a Perkin Elmer equipped with a 2P internal cooler and nitrogen purge. Each scan was programmed to run from -10°C to 200°C at 10°C / min and cool from 200°C to -10°C at 40°C / min. The glass transition temperature of each material was calculated using a single thermogram.

[0079] Differential Scanning Calorimetry (DSC) shows that epoxidized soybean oil (oil at room temperature) shifts to a higher temperature thermal event upon reaction with malic acid (and possibly tannic acid). In the complete system of epoxidized soybean oil + malic acid + tannic acid, there is a unique high temperature thermal event that is not associated with epoxidized soybean oil (below room temperature), tannic acid (>200°C alone), or malic acid. Epoxide titration

[0080] The remaining epoxy groups after the reaction were determined using a previously published ASTM method. The sample was titrated from a HBr stock solution until the color changed to the same as the control. The volume at which the color change was achieved was used to calculate the epoxide concentration. temperature

[0081] Standard Type T thermocouples are used to determine the approximate output temperature of household hair dryers and laboratory heat guns. Microscopic examination

[0082] Scanning electron microscope images were collected using a FEIQuanta 3D FEG instrument equipped with a gallium ion beam, an Everhart-Thornley detector and a typical accelerating voltage of 5 kV.

[0083] When the bonded joint was pulled apart, the Figure 7 ) were examined. A mix of adhesive and cohesive failure mechanisms were found in the epoxy and soy-mal-tan samples, but the differences between the two were clear. The epoxy showed a single, clean fracture with typical brittleness. The SEM images of the soy-mal-tan were more complex, with multiple stress lines providing evidence that the mechanical forces were distributed throughout the bulk of the material. Here, too, the soy-mal-tan appears to be less brittle than the epoxy.

[0084] Similar data for soy-mal-tan adhesives cured at room temperature, 70°C, and 180°C showed some progressive failure, indicating that the material was more ductile than its brittle commercial counterpart. The bonded joints were pulled apart and examined using a scanning electron microscope (SEM). Figure 7 ) were examined. A mix of adhesive and cohesive failure mechanisms were found in both the epoxy and soy-mal-tan samples, but the differences between the two were clear. The epoxy showed a single, clean fracture with typical brittleness. The SEM images of the soy-mal-tan were more complex, with multiple stress lines providing evidence that the mechanical forces were distributed throughout the bulk of the material. The soy-mal-tan appears to be less brittle than the epoxy.

[0085] These analytical methods indicate that soy-mal-tan is an extensively cross-linked matrix with all three components participating in the formation of covalent bonds. Epoxidized soybean oil and malic acid are coupled together via aliphatic ester bonds. Malic acid also reacts directly with tannic acid via aromatic ester bonds. The esters formed by the coupling of tannic acid with epoxidized soybean oil may be less prominent.

[0086] Lap shear test The adhesive composition was placed between two pieces of steel and cured at 180°C for 3, 18 or 24 hours. A 24-hour cure time provided the most promising results. After cooling, the joint was pulled to failure and the adhesion was quantified by dividing the maximum force at failure by the substrate overlap area.

[0087] Lap shear bonding provides a practical method to obtain a large amount of highly reproducible data. The joint is pulled apart and the maximum force at failure is divided by the substrate overlap area to quantify the adhesion. Epoxidized soybean oil and different composition ratios of tannic acid to glycerol or malic acid ( Figure 1 and Figure 2 ). Ultimately, the strongest system was a 1:0.4:0.5 mass ratio of epoxidized soybean oil:malic acid:tannic acid ("soy-mal-tan"). Each gram of soy-mal-tan contained about 0.4 grams of ethanol to dissolve the tannic acid.

[0088] Bonding strength To quantify the performance of soy-mal-tan, the adhesion of aluminum and steel was studied, with each material either polished or sandblasted. Figure 4A and 4B The new adhesive system showed very good bonding to each substrate, with structural strengths of 10 ± MPa for sandblasted aluminum and up to 16 ± 1 MPa for polished steel. Polished aluminum and sandblasted steel had structural strengths of about 13 MPa. The controls with only two components were significantly weaker or did not bond at all. The adhesion of epoxidized soybean oil to malic acid (no tannic acid) was 1.9 ± 0.4 MPa. Malic acid to tannic acid (no epoxidized soybean oil) formed a hard solid without any bonding ability. Epoxidized soybean oil to tannic acid (no malic acid) never cured to a solid.

[0089] Figure 6 Benchmarks compared to commercial products are also shown. Each glue was cured according to the manufacturer's instructions (e.g., time, temperature, use of clamps) and applied between the substrates in the same amount as soy-mal-tan (approximately 50 mg). The two most widely used bio-based adhesives are starch glue and hide glue. Figure 6A test using a sandblasted steel substrate showed that the bio-based products had a bond of approximately 0.7-1.5 MPa, an order of magnitude lower than soy-mal-tan. Among petroleum-derived products, Elmer's Glue-All (a polyvinyl acetate) and Gorilla Glue (a polyurethane) also had weaker bonds to sandblasted steel, approximately 1.0-1.2 MPa. The bonds of Super Glue (a cyanoacrylate, 10±2 MPa) and epoxy (13±2 MPa) were similar to soy-mal-tan (13±2 MPa). When used on a polished aluminum substrate, soy-mal-tan (13±1 MPa) exceeded the performance of all benchmarks, including Super Glue (9±4 MPa) and epoxy (7±1 MPa), which are generally considered to be the strongest types of structural adhesives1,2( Figure 6 B). Figure 6 C shows data for polytetrafluoroethylene (Teflon), an example of a low surface energy substrate. Here, the petroleum-based adhesive is the strongest (about 0.7–1 MPa), while soy-mal-tan (0.3 ± 0.1 MPa) outperforms the commercial bio-based product (about 0-0.05 MPa). Figure 4A , Figure 4B and Figure 5 Similar adhesion data are also provided for polished steel, sandblasted aluminum, and polyvinyl chloride (PVC) substrates.

[0090] Wood is particularly sustainable and plywood is one of the most widely used building materials. Reaction (5 days at 70°C) and curing (3 days at 120°C) conditions were modified for wood. Soy-mal-tan and most commercial systems achieve bonds that exceed wood strength ( Figure 6 D) From Figure 6 An intact adhesive joint and fractured wood can be seen in E. Although the conditions used to bond the wood were somewhat extreme, the observed substrate failure suggests that the parameters in actual use may be less demanding.

[0091] To explore a range of potential use conditions, soy-mal-tan (1:0.4:0.5 ratio) was applied between polished steel substrates and cured at room temperature for 24 hours. The bond strength was 0.7 ± 0.1 MPa, which is lower than the bond strength (16 ± 1 MPa) cured at 180°C for 6 hours. Alternatively, curing with a household hair dryer (approximately 65°C) for 5 minutes improved the bond to 1.2 ± 0.5 MPa. Using a higher temperature laboratory heat gun (approximately 200°C) for 5 minutes produced 4.1 ± 0.4 MPa. Table 1 shows similar data for polished aluminum, sandblasted aluminum, and sandblasted steel.

[0092] Products require a certain level of water resistance to ensure they remain intact when faced with harsh conditions. However, the water resistance of current industrial adhesives hinders debonding, component recycling, and degradation in landfills. Adhesives were tested for their water resistance. Bonded pairs of polished aluminum substrates were subjected to harsher conditions than many consumer products will experience. Joints with a 1.2 x 1.2 cm overlap were cured in air (70°C for 24 hours or 180°C for 6 hours) and then immersed in deionized water for different times, followed by measurement of bond strength. Fig.10 The results showed that after 24 hours underwater, soy-mal-tan maintained about 75-100% of its initial dry bond strength. Even after a week underwater, about 26-78% of the bond was retained. Similar experiments were conducted in artificial seawater with similar results, except that the rate of loss of bond over time was slightly faster ( Fig.10 ). These extreme cases, from deionized water to artificial seawater, cover most water quality conditions and indicate that the potential role of salt in debonding is small.

[0093] Control experiments showed that the performance of epoxy was also affected by salt water. Over the course of a week in water, the average strength of the joint did not change significantly; however, the error bars increased dramatically. Epoxy is known to swell in water. Here, the water contact made the epoxy more pliable and bubbles began to form, indicating that water had entered the material. Polished aluminum substrates bonded together with soy-mal-tan and cured at 180°C for 24 hours were immersed in boiling deionized water for 4 hours and subjected to harsh conditions ( Fig.11 ). The adhesion of these samples was 3±2 MPa, while the adhesion of the control samples left on the table was 15±1 MPa.

[0094] Industrial strength requirements for adhesive performance span a wide range, for example, packaging is not particularly challenging at 0.5-4MPa. At the other extreme are the high demands of automotive and aerospace structures, 5-30MPa. Making direct numerical comparisons can be tricky because variables include variations in joint configuration, substrate, environment, and service conditions. Nevertheless, soy-mal tan bonds metals at about 10-16MPa and is likely to meet the needs of the most demanding applications.

[0095] Lightweighting of cars and trucks is one example of where new materials may provide additional environmental benefits. Changing from heavy rivets and welds to adhesive bonding can reduce vehicle weight and improve fuel efficiency. Figure 4BShows how a pickup truck rocker panel is riveted to a section of steel bar to represent the vehicle frame. Also shown is an alternative method of joining the substrates using soy-mal-tan. Here, the adhesive is cured with a heat gun for five minutes. By replacing 36.9 grams of steel rivets with 0.9 grams of glue, the mass of adhesive in these assemblies was reduced by about 97%.

[0096] CO2 Emissions Data The production and curing of one ton of epoxy resin is estimated to generate about 5.8 tons of CO2 emissions. The production of one ton of soy-mal-tan consumes about 11 tons of CO2, and curing one ton of soy-mal-tan emits about 6.6 tons of CO2. Therefore, it is estimated that the production and use of one ton of soy-mal-tan absorbs about 4.4 tons of CO2.

[0097] Furthermore, any embodiments described in the following list of clauses are considered to be part of the present invention. A. An adhesive composition comprising (i) epoxidized oil (EO), (ii) a nucleophile and (iii) a phenolic compound. B. The adhesive composition of clause A, wherein the epoxidized oil is epoxidized soybean oil. C. The adhesive composition of clause A, wherein the nucleophile comprises a compound having a moiety selected from the group consisting of an acid, an alcohol, an amine, and a thiol. D. The adhesive composition of clause C, wherein the nucleophile is selected from fumaric acid, glycerol, malic acid, succinic acid, or a combination thereof. E. The adhesive composition of clause D, wherein the nucleophile is malic acid. F. The adhesive composition of clause A, wherein the phenolic compound is selected from catechol, gallic acid, gallol, lignin, tannic acid, or a combination thereof. G. The adhesive composition of clause F, wherein the phenolic compound is tannic acid. H. The adhesive composition of clause A or G, wherein the composition further comprises a solvent. I. The adhesive composition of clause H, wherein the solvent is selected from the group consisting of alcohol, water, chloroform, dichloromethane, dimethyl sulfoxide, and dimethylformamide. J. The adhesive composition of clause I, wherein the solvent is ethanol or methanol. K. The adhesive composition of clause A, wherein the mass ratio of the EO, the nucleophile, and the phenolic compound is from about 1:0.1:0.1 to about 1:10:10. L. An adhesive composition consisting essentially of (i) epoxidized soybean oil (ESO), (ii) malic acid, (iii) tannic acid, and (iv) ethanol. M. The adhesive composition of clause L, wherein the mass ratio of ESO, malic acid, and tannic acid is from about 1:0.1:0.1 to about 1:10:10. N. An adhesive substrate comprising the adhesive composition of any one of clauses AM. O. The bonded substrate of clause N, wherein the substrate is exposed to dry, wet, moist or underwater conditions. P. The bonding substrate of clause O, wherein the substrate is metal, wood, plastic, ceramic, or any combination thereof. Q. The bonding substrate of item P, wherein the metal substrate is steel or aluminum. R. A method of making the adhesive composition of clause A or L, the method comprising: i) heating epoxidized oil (EO); ii) mixing a phenolic compound with the epoxidized oil of step (i) to obtain a solution, wherein the phenolic compound optionally in the form of a solution in a solvent; iii) adding a nucleophile to the solution of step (ii) and heating the solution; and iv) cooling the solution to room temperature, Thus, the adhesive composition is obtained. S. The method of clause R, wherein the EO is epoxidized soybean oil. T. The process of clause R, wherein the EO and the solution of step (iii) are heated at a temperature of about 70°C to about 90°C. U. The method of clause R, wherein the solvent is selected from the group consisting of alcohol, water, chloroform, dichloromethane, dimethyl sulfoxide and dimethylformamide. V. The method of clause R, wherein the nucleophile is a compound comprising a moiety selected from the group consisting of an acid, an alcohol, an amine, and a thiol. W. The method of clause V, wherein the nucleophile is selected from fumaric acid, glycerol, malic acid, succinic acid, or a combination thereof. X. The method of clause W, wherein the nucleophile is malic acid. Y. The method of clause R, wherein the phenolic compound is selected from catechol, gallic acid, gallol, lignin, tannic acid, or a combination thereof. Z. The method of clause Y, wherein the phenolic compound is tannic acid. A'. A method of using the adhesive composition of any of clauses AM, the method comprising applying the adhesive composition to at least a first substrate to be bonded to at least a second substrate, and bonding the at least first substrate and the at least second substrate to each other. B'. The method of clause A', further comprising applying the adhesive composition to the at least second substrate prior to bonding the at least first substrate and the at least second substrate. C'. The method of clause A' or B', wherein the at least first substrate and / or the at least second substrate is exposed to dry, damp, wet or underwater conditions. D'. The method of clause A' or B', wherein the at least first substrate and / or the at least second substrate is metal, wood, plastic, ceramic, or any combination thereof. E'. The method of clause D', wherein the metal is steel or aluminum.

[0098] As used herein, the following terms and phrases shall have the following meanings. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art.

[0099] The term "about" can allow for a certain degree of variability in a value or range, for example, within 10%, within 5%, or within 1% of a stated value or stated limit of a range.

[0100] The term "substantially" can allow for a certain degree of variability in values ​​or ranges, for example, within 90%, within 95%, or within 99% of a stated value or stated limit of a range.

[0101] The terms "a", "an" or "the" are used to include one or more than one, unless the context clearly dictates otherwise. The term "or" is used to refer to a non-exclusive "or" unless otherwise specified. In addition, the words or terms used herein, unless otherwise defined, are used for descriptive purposes only and not for limitation. The use of any section headings is intended to aid in the reading of this document and should not be construed as limiting. In addition, information associated with a section heading may appear within or outside of that particular section. The terms "including" and "having" are defined as comprising (i.e., open language).

[0102] In addition, all publications, patents, and patent documents mentioned in this document are incorporated herein by reference in their entirety, as if individually incorporated by reference. In the event of an inconsistency in the usage of this document and those documents incorporated by reference, the usage in the incorporated references should be considered supplementary to that of this document; for irreconcilable inconsistencies, the usage in this document controls.

[0103] Those skilled in the art will recognize that numerous modifications may be made to the specific embodiments described above. The embodiments should not be limited to the specific limitations described. Other embodiments are also possible.

[0104] The scope of the method and apparatus of the present invention is intended to be limited by the appended claims. However, it must be understood that the present disclosure may be implemented in a manner different from that specifically explained and illustrated without departing from the spirit or scope of the present disclosure. It will be appreciated by those skilled in the art that various alternatives to the embodiments described herein may be adopted when implementing the claims without departing from the spirit and scope defined by the appended claims.

Claims

1. An adhesive composition comprising (i) epoxidized oil (EO), (ii) a nucleophile and (iii) a phenolic compound.

2. The adhesive composition according to claim 1, wherein the epoxidized oil is epoxidized soybean oil. 3 . The adhesive composition of claim 1 , wherein the nucleophile is a compound comprising a moiety selected from the group consisting of an acid, an alcohol, an amine, and a thiol.

4. The adhesive composition according to claim 3, wherein the nucleophile is selected from fumaric acid, glycerol, malic acid, succinic acid or a combination thereof.

5. The adhesive composition of claim 4, wherein the nucleophile is malic acid.

6. The adhesive composition according to claim 1, wherein the phenolic compound is selected from catechol, gallic acid, gallol, lignin, tannic acid or a combination thereof. The adhesive composition according to claim 6 , wherein the phenolic compound is tannic acid.

8. The adhesive composition according to claim 1 or 7, wherein the composition further comprises a solvent.

9. The adhesive composition according to claim 8, wherein the solvent is selected from alcohol, water, chloroform, dichloromethane, dimethyl sulfoxide and dimethylformamide.

10. The adhesive composition according to claim 9, wherein the solvent is ethanol or methanol. 11 . The adhesive composition of claim 1 , wherein the EO, the nucleophile, and the phenolic compound are present in a mass ratio of about 1:0.1:0.1 to about 1:10:

10.

12. An adhesive composition consisting essentially of (i) epoxidized soybean oil (ESO), (ii) malic acid, (iii) tannic acid, and (iv) ethanol.

13. The adhesive composition of claim 12, wherein the ESO, malic acid, and tannic acid are present in a mass ratio of about 1:0.1:0.1 to about 1:10:

10.

14. An adhesive substrate comprising the adhesive composition of any one of claims 1 to 13.

15. The bonded substrate of claim 14, wherein the substrate is exposed to dry, wet, moist or underwater conditions.

16. The bonded substrate of claim 14, wherein the substrate is metal, wood, plastic, ceramic, or any combination thereof.

17. The bonded substrate of claim 16, wherein the metal substrate is steel or aluminum.

18. A method for producing the adhesive composition of claim 1 or 12, the method comprising: i) heating epoxidized oil (EO); ii) mixing a phenolic compound with the epoxidized oil of step (i) to obtain a solution, wherein the phenolic compound is optionally present in the form of a solution in a solvent; iii) adding a nucleophile to the solution of step (ii) and heating the solution; as well as iv) cooling the solution to room temperature, Thus, the adhesive composition is obtained.

19. The method of claim 18, wherein the EO is epoxidized soybean oil.

20. The method of claim 18, wherein the EO and the solution of step (iii) are heated at a temperature of about 70°C to about 90°C.

21. The method of claim 18, wherein the solvent is selected from the group consisting of alcohol, water, chloroform, dichloromethane, dimethyl sulfoxide and dimethylformamide.

22. The method of claim 18, wherein the nucleophile is a compound comprising a moiety selected from the group consisting of an acid, an alcohol, an amine, and a thiol.

23. The method of claim 22, wherein the nucleophile is selected from fumaric acid, glycerol, malic acid, succinic acid, or a combination thereof.

24. The method of claim 23, wherein the nucleophile is malic acid.

25. The method of claim 18, wherein the phenolic compound is selected from catechol, gallic acid, gallol, lignin, tannic acid, or a combination thereof.

26. The method of claim 25, wherein the phenolic compound is tannic acid.

27. A method of using the adhesive composition of any one of claims 1-13, the method comprising applying the adhesive composition to at least a first substrate to be bonded to at least a second substrate, and bonding the at least first substrate and the at least second substrate to each other.

28. The method of claim 27, further comprising applying the adhesive composition to the at least second substrate prior to bonding the at least first substrate and the at least second substrate.

29. The method of claim 27 or 28, wherein the at least first substrate and / or the at least second substrate is exposed to dry, damp, wet or underwater conditions.

30. The method of claim 27 or 28, wherein the at least first substrate and / or the at least second substrate is metal, wood, plastic, ceramic or any combination thereof.

31. The method of claim 30, wherein the metal is steel or aluminum.